2012
DOI: 10.1556/eujmi.2.2012.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Quorum sensing dependent phenotypes and their molecular mechanisms inCampylobacterales

Abstract: Quorum sensing comprises the mechanism of communication between numerous bacteria via small signalling molecules, termed autoinducers (AI). Using quorum sensing, bacteria can regulate the expression of multiple genes involved in virulence, toxin production, motility, chemotaxis and biofilm formation, thus contributing to adaptation as well as colonisation. The current understanding of the role of quorum sensing in the lifecycle of Campylobacterales is still incomplete. Campylobacterales belong to the class of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 53 publications
(105 reference statements)
0
20
0
1
Order By: Relevance
“…A total of 605 words mapped to genes that have previously been shown to have a functional association with increased biofilm production, such as motility (Svensson et al ., ), chemotaxis (Golz et al ., ), capsule production (Malde et al ., ) and protein glycosylation (Joshua et al ., ; Guerry, ) (http://onlinelibrary.wiley.com/doi/10.1111/1462-2920.13051/suppinfo; highlighted in Fig. B).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 605 words mapped to genes that have previously been shown to have a functional association with increased biofilm production, such as motility (Svensson et al ., ), chemotaxis (Golz et al ., ), capsule production (Malde et al ., ) and protein glycosylation (Joshua et al ., ; Guerry, ) (http://onlinelibrary.wiley.com/doi/10.1111/1462-2920.13051/suppinfo; highlighted in Fig. B).…”
Section: Resultsmentioning
confidence: 99%
“…This process affects bacterial populations and determines the expression of genes regulating virulence, toxin production, motility, chemotaxis, biofilm production, and bacterial competition (secretion systems [T3SS and T6SS]) ( Fig. 2), which may contribute to bacterial adaptation and colonization (218). In this review, we consider proteins from the QS system and secretion systems (T3SS and T6SS) due to their association with the development of persister cells, as described for pathogens such as P. aeruginosa and Mycobacterium spp.…”
Section: Qs and Secretion Systemsmentioning
confidence: 99%
“…Nonetheless, the anti-biofilm activity of resveratrol against several pathogens has already been described, being suggested that this activity may be related to the regulation of biofilm-related genes such as adhesion, motility or even QS genes (Augustine, Goel, Sivakumar, Kumar, & Thomas, 2014;Lee, Kim, Ryu, Cho, & Lee, 2014a;Lee, Lee, Ryu, Cho, & Lee, 2014b). So, the antibiofilm activity of the IC could be explained by the effect of the active compound, resveratrol, in genes associated with biofilms formation, and the effect on the pre-establish biofilm could be mainly due to the effect on QS, since this process has been documented to play a role in the formation and maintenance of Campylobacter biofilms (Gölz, Sharbati, Backert, & Alter, 2012;Reeser et al, 2007).…”
Section: Anti-qs Activity Of the Inclusion Complexmentioning
confidence: 99%